Comprehensive Analysis of an Individualized Immune-Related lncRNA Pair Signature in Gastric Cancer - Nie, Chuang; Zhai, Jiabao; Wang, Qi; Zhu, Xiaojie; Xiang, Guanghui; Liu, Chang; Liu, Tianyu; Wang, Wanyu; Wang, Yimin; Zhao, Yashuang; Tian, Wenjing; Xue, Yingwei; et al. (Frontiers in Cell and Developmental Biology, 2022)
Long noncoding RNAs (lncRNAs) have diverse functions, including immune regulation. Increasing studies have reported immune-related lncRNAs in the prognosis of multiple cancers. In this study, we developed an individualized signature containing 13 immune-related lncRNA pairs (IRLPs) which could predict the overall survival, disease-free survival, progression-free survival, and disease-specific survival of gastric cancer (GC) patients in The Cancer Genome Atlas (TCGA) cohort, and internal and external validations, signature comparisons, and subgroup analyses further confirmed its superiority, stability, and generalizability. Notably, this signature also showed good applicability in discriminating the prognosis of pan-cancer patients. Then, we constructed and validated a nomogram for overall survival based on the signature and clinical factors, which allowed more accurate predictions of GC prognosis. In addition, we revealed that the low survival rate of patients with high-risk scores may be due to their aggressive clinical features, enriched cancer-related signaling pathways, the infiltration of specific immunosuppressive cells, and low tumor mutation burden. We further predicted obviously worse immunotherapeutic responses in the high-risk groups and identified some candidate compounds targeting GC risk group differentiation. This signature based on the IRLPs may be promising for predicting the survival outcomes and immunotherapeutic responses of GC patients in clinical practice.